2020
DOI: 10.1111/dth.13861
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options for autoimmune bullous dermatoses other than systemic steroids: A systematic review and network meta‐analysis

Abstract: Autoimmune blistering diseases can eventually cause life-threatening complications if left untreated. Although there is no cure for these bullous diseases; their therapy is based on suppressing the immune system to cease the de novo formation of the generated antibodies. The current study aimed to assess the safety and efficacy of using standing alone alternative therapies beyond systemic steroids for management of autoimmune bullous diseases. We searched six literature databases for both randomized and quasi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…For example, the BLISTER study has shown that starting patients on doxycycline is non-inferior to standard treatment with oral prednisolone for short-term blister control in bullous pemphigoid and significantly safer in the long-term ( 26 ). A recent systematic review and network meta-analysis concluded that combined doxycycline and nicotinamides are a safer and more effective option for extensive bullous pemphigoid patients as compared to usual use of systemic steroids and that minocycline may be a safer promising option for renal impairment patients ( 27 ). The beneficial non-antibiotic properties of TCNs in bullous pemphigoid and other diseases are far from being clear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the BLISTER study has shown that starting patients on doxycycline is non-inferior to standard treatment with oral prednisolone for short-term blister control in bullous pemphigoid and significantly safer in the long-term ( 26 ). A recent systematic review and network meta-analysis concluded that combined doxycycline and nicotinamides are a safer and more effective option for extensive bullous pemphigoid patients as compared to usual use of systemic steroids and that minocycline may be a safer promising option for renal impairment patients ( 27 ). The beneficial non-antibiotic properties of TCNs in bullous pemphigoid and other diseases are far from being clear.…”
Section: Introductionmentioning
confidence: 99%